Kemampuan Pemecahan Masalah Siswa Sma Pada Pembelajaran Problem-Based Learning Pendekatanculturally Responsive Teaching Dengan Strategi Scaffolding - Agrota Shoit (Jurnal THEOREMS (The Original Research of Mathematics), 2023)
Problem-solving ability is a very important ability. But in reality, this ability still needs to be optimized. The purpose of this research is to find out the effectiveness of problem-based learning with a culturally responsive teaching approach with a scaffolding strategy on the problem-solving abilities of high school students. The study population was 11th-grade students divided into 8 classes and the sample was selected using cluster random sampling technique. This research method uses quantitative research with a quasi-experiment design. The data collection technique uses a problem-solving ability test. Research shows that the problem-solving ability in the experimental class achieves classical mastery with a percentage of classical mastery in the experimental class of 81%, while the problem-solving ability in the control class has not yet reached classical mastery. In addition, the average problem-solving ability of the experimental class is better than the average problem-solving ability of the control class, this is evidenced by the t_count=2.385>t_table=1.994. In other words, problem-based learning with a culturally responsive teaching approach with a scaffolding strategy is effective for students' mathematical problem-solving abilities.Keywords: Problem-Solving Ability, Problem-Based Learning, Culturally Responsive Teaching, Scaffolding.